Designing and implementation of variance-dependent Goldstein radar interferogram filtering - Wang, Qi-jie; Zhang, Xiao-hu; Zhu, Jian-jun; Hu, Jun (Journal of Central South University, 2014)
The variance-dependent Goldstein radar interferogram filter takes into account the information of both interferometric coherence and multilook factors, and can produce very consistent results for interferograms generated under a wide variety of multilook factors and with very different noise level. However, the filter is a bit complicated and its application is still very limited. We present the designing and implementation of the variance-dependent Goldstein radar interferogram filtering, emphasizing on the logic flow, the generation of look-up table, the determination of filtering parameter, and the handling of edge information loss. Experiments with real interferograms are provided to demonstrate the applications of the designed filtering. Comparisons with the result of the coherence-dependent Goldstein filter show that improvements from 18.4% to 36.9% are achieved when the variance-dependent filter is used, and the noisier the interferogram, the greater the improvement.